An interactive dynamic simulation model of a university management system - Diker, Vedat Güçlü. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1995., 1995)
The main objective of this research is to construct an interactive simulation model, on which a range of problems concerning the academic aspects of a university management system can be analyzed and certain policies for overcoming these problems can be tested. More specifically, the model focuses on long-term, strategic university problems that are dynamic and persistent in nature. The model generates numerous performance measures about the three fundamental activities of a university, namely, teaching, research and professional projects. To construct such a game, a system dynamics model of the academic aspects of a university system is built. The model is validated and verified by standard tests. After these tests, some illustrative scenario experiments are done to demonstrate the analysis capabilities of the model. Next, the necessary changes are made on the model to construct the interactive gaming version and the gaming interface is programmed. After the game is validated, it is played by a group of faculty, members, teaching assistants and students. Finally, the game results of these players are analyzed and compared. Differences in performances reveal that players with different orientations focus on different performance measures in making decisions.
Keywords: Universities and colleges -- Administration.